Different mutations are responsible for the elevated sister-chromatid exchange frequencies characteristic of Bloom's syndrome and hamster EM9 cells. - Ray, J H (1987)
Experimental hybridization of cultured cells was employed to determine whether the strikingly elevated rates of sister-chromatid exchange (SCE) exhibited by Bloom's syndrome (BS) and hamster cell line EM9 have the same or different bases. Seventeen cell lines were developed from polyethylene glycol-treated mixtures of BS and EM9 cells. Cytogenetic analysis proved the hybrid nature of 12 of the lines; 9 of those 12 exhibited low (normal) numbers of SCEs, signifying complementation. The parental BS and EM9 cells, although resembling each other in exhibiting very high SCE frequencies in BrdUrd-containing medium, differ from one another with respect to their proliferative abilities in such medium, the EM9 cells but not the BS cells being exquisitely hypersensitive to BrdUrd. In the low-SCE hybrid lines, hypersensitivity to growth in BrdUrd-containing medium was restored to normal whereas the hypersensitivity was retained by the high-SCE hybrids. It is concluded, first, that the mutations in BS and EM9 cells are different and, second, that both the elevated SCE frequency and the excessive BrdUrd hypersensitivity of EM9 cells are due to the same mutation.